Determination of the management of a patient with stable ischemic heart disease according to the data of fractional flow reserve study - M.V. Stan; A.V. Khokhlov; О.J. Zharinov; O.V. Zelenchuk; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
Revascularization of coronary arteries is a key method of the contemporary treatment of patients with atherosclerotic coronary stenoses. However, at an intermediate degree of stenosis, the decision on the appropriateness of revascularization may depend on additional studies of the functional significance of anatomical changes. The study of the fractional flow reserve (FFR) may have a special role in such cases. The publication considers an example of determining the extent of endovascular revascularization in a patient with multivessel lesions of the coronary arteries, with intermediate severity of stenosis. The combination of functional class II angina with unclear result of a stress test, as well as the lack of optimal drug therapy at the time of examination led to the decision to assess physiological significance of all existing stenoses by determining the FFR. Based on the FFR, it was decided to continue monitoring the patient, prescribe optimal medical therapy and refrain from revascularization intervention until the evaluation of its results